Cardiac remodeling and dysfunction in childhood obesity: a cardiovascular magnetic resonance study. Issue 1 (December 2016) - Jing, Linyuan; Binkley, Cassi; Suever, Jonathan; Umasankar, Nivedita; Haggerty, Christopher; Rich, Jennifer; Nevius, Christopher; Wehner, Gregory; Hamlet, Sean; Powell, David; Radulescu, Aurelia; Kirchner, H.; et al.
Abstract Background Obesity affects nearly one in five children and is associated with increased risk of premature death. Obesity-related heart disease contributes to premature death. We aimed to use cardiovascular magnetic resonance (CMR) to comprehensively characterize the changes in cardiac geometry and function in obese children. Methods and results Forty-one obese/overweight (age 12 ± 3 years, 56 % female) and 29 healthy weight children (age 14 ± 3 years, 41 % female) underwent CMR, including both standard cine imaging and displacement encoded imaging, for a complete assessment of left ventricular (LV) structure and function. After adjusting for age, LV mass index was 23 % greater (27 ± 4 g/m2.7 vs 22 ± 3 g/m2.7, p <0.001) and the LV myocardium was 10 % thicker (5.6 ± 0.8 mm vs 5.1 ± 0.8 mm, p <0.001) in the obese/overweight children. This evidence of cardiac remodeling was present in obese children as young as age 8. Twenty four percent of obese/overweight children had concentric hypertrophy, 59 % had normal geometry and 17 % had either eccentric hypertrophy or concentric remodeling. LV mass index, thickness, ejection fraction and peak longitudinal and circumferential strains all correlated with epicardial adipose tissue after adjusting for height and gender (allp <0.05). Peak longitudinal and circumferential strains showed a significant relationship with the type of LV remodeling, and were most impaired in children with concentric hypertrophy (p <0.001 andp = 0.003, respectively). Conclusions Obese children show evidence of significant cardiac remodeling and dysfunction, which begins as young as age 8. Obese children with concentric hypertrophy and impaired strain may represent a particularly high risk subgroup that demands further investigation.